2006
DOI: 10.1093/dnares/dsl010
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen Induction of Sugar Catabolic Gene Expression in Synechocystis sp. PCC 6803

Abstract: Nitrogen starvation requires cells to change their transcriptome in order to cope with this essential nutrient limitation. Here, using microarray analysis, we investigated changes in transcript profiles following nitrogen depletion in the unicellular cyanobacterium Synechocystis sp. PCC 6803. Results revealed that genes for sugar catabolic pathways including glycolysis, oxidative pentose phosphate (OPP) pathway, and glycogen catabolism were induced by nitrogen depletion, and activities of glucose-6-phosphate d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

16
150
1
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 128 publications
(168 citation statements)
references
References 40 publications
16
150
1
1
Order By: Relevance
“…9 Later it was also shown to be induced under other conditions that alter the electron transport rate around PSI, such as sulfur and nitrogen starvation or low oxygen. [10][11][12] We have shown that copper is strictly required for these inductions, suggesting that these are indirect effects of reduction of photosynthetic electron transport. Plastocyanin, which is the main copper containing protein in Synechocystis, it is also the major difference between photosynthetic electron transport chains in copper replete and copper free medium.…”
mentioning
confidence: 86%
“…9 Later it was also shown to be induced under other conditions that alter the electron transport rate around PSI, such as sulfur and nitrogen starvation or low oxygen. [10][11][12] We have shown that copper is strictly required for these inductions, suggesting that these are indirect effects of reduction of photosynthetic electron transport. Plastocyanin, which is the main copper containing protein in Synechocystis, it is also the major difference between photosynthetic electron transport chains in copper replete and copper free medium.…”
mentioning
confidence: 86%
“…However, cyanobacteria contain single-helix proteins of the Cab family, named SCPs (small Cab-like proteins) or Hli (high light-induced proteins) (6). We will use the SCP designation here, as the corresponding genes are induced not only at high light intensity (7)(8)(9)(10), but also in other stress conditions, such as at low temperature (11), low pH (12), nitrogen and sulfur starvation (8,13), salt and hyperosmotic stresses (11, 14 -16), presence of hydrogen peroxide (17), or inhibitors of photosynthetic electron transport (18).…”
mentioning
confidence: 99%
“…Earlier we have shown that synthesis and degradation rates of porphyrins can be measured in Synechocystis cells in situ by analyzing 15 N or 13 C isotope incorporation into pigments (27,28). In this study, stable isotope labeling has been used to perform a systematic survey of mutants lacking single or multiple SCPs with respect to their ability to synthesize, degrade, and reuse chlorophyll under different growth conditions in the light.…”
mentioning
confidence: 99%
“…PCC 6803 (Fig. 3B), which is up-regulated by nitrogen deprivation (26). The NrrA binding region of the hetR promoter has been determined by DNase I footprinting assays (14), and a similar sequence (AATGTCA) was found within the region (Fig.…”
Section: Nrra Positively Regulates Expression Of the Glgp1mentioning
confidence: 89%
“…In Synechocystis PCC 6803, rre37, an ortholog of nrrA, and sigE are involved in regulation of sugar catabolism (26,27). Rre37 and SigE independently regulate sugar catabolism under the control of NtcA in contrast to Anabaena PCC 7120, and transcriptional regulation of sigE is exclusively dependent on NtcA (30).…”
Section: Discussionmentioning
confidence: 99%